Crystallographic insights into the self‐assembly of KLVFF amyloid‐beta peptides. Issue 5 (16th February 2018) - Pizzi, Andrea; Dichiarante, Valentina; Terraneo, Giancarlo; Metrangolo, Pierangelo
Abstract: Amyloidogenic peptide fragment KLVFF (H2 N‐Lys‐Leu‐Val‐Phe‐Phe‐COOH, Aβ16‐20 ), the core‐sequence of the polypeptide Aβ40, is a well‐studied model for amyloid formation. However, due to its low crystallinity, detailed atomic information of KLVFF structure is lacking. Here we report the high‐resolution single‐crystal X‐ray structure of two monohalogenated KLVFF derivatives, KLVFF(I) and KLVFF(Br). The obtained results highlight how halogenation is a good strategy to promote crystallization and facilitate the phase determination of KLVFF(I) and KLVFF(Br) fragments. Detailed structural studies on the packing features of both monohalogenated derivatives reveal the role of the halogen atoms showing that when they are positioned on the Phe aromatic moiety at the C‐terminus they do not form halogen bonds and thus do not produce any extra stabilization of the β‐sheet in the self‐assembly process. The structural evidences gained from these studies corroborate the various polymorphic nanostructures of the halogenated variants of KLVFF and confirm the possibility to use halogenation as innovative strategy to tune the morphology of this pentapeptide. Abstract :